Influence of process parameters on bioprotein production from palm kernel cake and seaweed using solid state fermentation - Ilias, Nurul Najihah; Jamal, Parveen; Jaswir, Irwandi; Sulaiman, Sarina (2015)
The factors that influenced the protein content of the biomass produced after the solid state fermentation were studied. Two types of raw materials (palm kernel cake and seaweed) which were already proven to contain various types of nutritional compounds, had been used as substrates for supporting the growth of two compatible microorganisms, Phanerochaete chrysosporium and Candida utilis that were used in the fermentation process. The effect of fermentation parameters (initial pH, moisture content and inoculum size) on the amount of bioprotein produced after the fermentation was determined. Maximum bioprotein content found in the final product of fermentation process was 247.1 mg/g with the optimum parameters obtained were 3.5, 71.0% and 8.0% for initial pH, moisture content and inoculum size respectively. The other factors that influenced the fermentation process such as time and temperature of incubation were also studied. Results showed that the temperature of 28°C and incubation of six days gave the highest amount of bioprotein content in the final product. The effects of the experimental fish feed towards the performance of fish were also studied.